Development and study of a visco-elastic gel with controlled destruction times for killing oil wells - Dmitriy A. Martyushev; Suresh Kumar Govindarajan (Journal of King Saud University: Engineering Sciences)
Well killing remains to be the critical technological stage before proceeding with workover operations. Well killing using Visco-Elastic Gel (VEG) has been found to preserve and reinstate the filtration characteristics of bottom-hole formation zone efficiently. Since, these methods exclude the possibility of penetration of well-killing fluids into the reservoirs, the natural permeability of the reservoir retained. In this article, the authors have reported for the first time about a new VEG with controlled fracture times that remains appropriate for killing oil wells associated with both terrigenous carbonate reservoir operations. A distinctive feature of the proposed technology using a VEG with adjustable degradation times (can vary from 3 to 120 h) is that it requires a relatively smaller volumes of the composition in comparison with that of the conventional technologies. As a result, a significant reduction in the negative impact on the reservoir is achieved resulting from a relatively low penetrating ability of the proposed VEG. High structural properties of the VEG make it possible to reliably block the overlapped reservoir interval and it excludes the penetration of process fluid into the reservoir. In addition, it also eliminates the flow of formation fluid from the reservoir, which is absolutely necessary for trouble-free repairing work. It was found from the present study that the use of a breaker of a particular, single type does not provide the desired results and in the present study, the authors have deduced a relatively complex breaker based on peroxyhydrate and citric acid with a 1:1 ratio. The introduction of the encapsulated peroxyhydrate at the stage of preparation of the VEG ensures monodispersity of its dispersion characteristics. The developed VEG was successfully tested in 32 wells of oil fields in the Perm Krai fields in Russia. The well killing technology developed and described in this article using a VEG with adjustable destruction times has successfully been applied in the fields of the Perm Krai. The economic effect from the application of this technology was found to be $6.000 per well.